LA CORRUPCIÓN DESDE UNA MIRADA METAJURÍDICA Artículo de reflexión sobre la corrupción por psicopatía (2021)
In Colombia, there is a legal framework that includes regulatory and legal developments aimed at to fight against the phenomenon of corruption, however, it still persists and is presented to the within entities at the national, regional and local levels. Reason why the present article intends to see corruption from a much deeper perspective, that is, from a psychological perspective, which implies establishing a form of corruption control by psychopathy and that acts of corruption are not committed, on the understanding that understanding of a phenomenon is an unavoidable requirement for its transformation.